Silica-based ceramics toward electromagnetic microwave absorption. Issue 15 (December 2021) - Zeng, Xiaojun; Li, Eugene; Xia, Guohua; Xie, Nuohua; Shen, Zong-Yang; Moskovits, Martin; Yu, Ronghai
Highlights: Discuss the definition and characteristics, classification, synthetic methods, and potential applications for ceramics. Highlight recent achievements in fabricating the silica-based ceramics for EMW absorption. Focus on the component and structural design of ceramic absorbers, which correlate them with EMW absorption performance. Comment on prospects and ongoing challenges of ceramic absorbers for EMW absorption. Abstract: Silica-based ceramics have been explored extensively as a class of versatile materials for various applications in architecture, catalysis, energy, machinery, and biomedical engineering. Nevertheless, comprehensive information on silica-based ceramic and electromagnetic microwave (EMW) absorption is scarce, although excellent progress has been made in this field. Here, recent progress in the investigation of silica-based ceramics toward EMW absorption is reviewed. We first introduced the basis of ceramics (characteristics, classification, synthetic methods, potential applications). Subsequently, the silica-based ceramics, including Si-based oxides and alloys, SiOC/SiC/Si3 N4 /SiCN-based composite, Ti3 SiC2 and composite for EMW absorption were systematically summarized. Notably, the fabrication strategies, absorption properties, and mechanisms of silica-based ceramics are described in detail, with a focus on structure and component design. Lastly, the prospects and ongoing challenges of this field in the future are presented. This review is expected to learn from the past and achieve progress toward the future of silica-based ceramic for EMW absorption.